فاعلية استخدام الوسائل البصرية كأدوات تعليمية في تدريس اللغة لإنجليزية في المدارس الابتدائية الليبية - El-meshry, Abeer El-waer Nasser (Al-Qurtas, 2025)
This paper aims to examine the impact of visual aids on English language teaching in primary schools in Libya. Visual aids play an essential role in enhancing students’ comprehension, engagement, and retention of language concepts. However, many teachers do not utilize them effectively, leading to barriers in the teaching process and affecting learning outcomes. This research explores teachers’ perceptions of visual aids and evaluates their effectiveness in improving English language acquisition. The study employs a descriptive research design, using a questionnaire to collect quantitative data from 20 teachers in two public schools in Tiji city. Findings indicate that visual aids significantly enhance students’ motivation, participation, and understanding . The results confirm that visual aids positively influence the teaching process and student engagement. Teachers agree that visual tools simplify complex concepts, improve classroom interaction, and support long- term retention of information. Based on these findings, the study recommends regular integration of visual aids, teacher training programs, diversification of materials to suit different learning styles, and the adoption of modern technology such as smart boards and augmented reality applications.